Disseminated intravascular coagulation, associated factors and clinical outcomes among critically Ill septic adults admitted to a tertiary hospital in Ethiopia: A prospective longitudinal study - Girum Tesfaye Kiya; Zeleke Mekonnen; Elsah Tegene Asefa; Gedion Milkias; Edosa Tadasa; Edosa Kejela; Iyasu Demeke; Aragaw Fiseha; Gemeda Abebe (PLoS ONE, 2025)
Background Despite the established link between sepsis and disseminated intravascular coagulation (DIC), data on the prevalence of DIC, associated factors and patient outcomes in sepsis patients are inadequate in resource-limited settings. Therefore, the present study aimed to determine the magnitude of DIC and associated factors and mortality and predictors in septic adults admitted to intensive care units (ICUs). Methods A prospective longitudinal study involving adults admitted to intensive care units was conducted. A structured checklist and questionnaire were used to collect patient demographic and clinical data. Blood samples were collected on days 1, 3, and 5 of admission for all laboratory analyses. A DIC diagnosis was made on the basis of the Japanese Association for Acute Medicine (JAAM) score. Descriptive statistics, multivariable logistic regression analysis, receiver operating characteristic (ROC) curve analysis and Kaplan‒Meier survival analysis were employed in this study. Results The overall prevalence of DIC in sepsis patients was 38 (25.7%). There were 24 (16.2%) patients who developed DIC on day 1 of admission, while 20 (19.4%) and 9 (12.9%) patients developed DIC on day 3 and day 5 of admission, respectively. Increased aspartate transaminase (AST) (AOR: 4.39; 95% CI: 1.75–11.01), thrombocytopenia (AOR: 6.04; 95% CI: 2.41–15.12), and prolonged prothrombin time (PT) (AOR: 3.40; 95% CI: 1.36–8.51) were independent predictors of DIC in sepsis patients. There was no statistically significant difference in survival between patients with and without DIC (p < 0.328). The JAAM score at ICU admission predicted ICU mortality (AUC: 0.787; 95% CI: 0.624–0.950). Conclusion A quarter of ICU-admitted septic adults developed DIC. The incidence was notably greater by the third day after admission, highlighting the importance of closely monitoring these patients for DIC progression. Elevated AST liver enzyme levels, thrombocytopenia, and prolonged PT are linked to the development of DIC. Changes in these variables could prompt further examination for DIC. The mortality rate did not significantly differ between septic patients with and without DIC. The JAAM score used to diagnose DIC in sepsis patients can serve as a predictor of ICU mortality in sepsis patients with DIC.